ESTUDIOS SOBRE LAS RESPUESTAS COVULSIVANTES EXPERIMENTALES Y SUS MODIFICACIONES VII LIPIDOS Y BARRERA HEMATOENCEFALICA - OBRADOR ALCALDE, S; ARROYO, S; ALVAREZ, JAVIER A (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1945)
An extract of cihuapahtli, a plant long popular medicinally in its native Mexico, was studied for its effects on the nongravid and gravid uterus of the cat Intravenous injn produced an increase in the amplitude of the spontaneous rhythmic uterine contra
BOL INST ESTUD MED BIOL
Keywords: ESTUDIOS, RESPUESTAS, COVULSIVANTES, EXPERIMENTALES, LIPIDOS, BARRERA, HEMATOENCEFALICA; CIENCIAS MEDICAS; MEDICINA INTERNA; NEUROLOGIA